Constraints of Adoption of Agricultural Extension Package Technologies on Sorghum Crop Production at Smallholder Farm Household Level: Evidence from West Hararghe Zone, Oromia, Ethiopia - Muhammed Shako; Adunea Dinku; Waktola Mosisa (Advances in Agriculture)
An effective and efficient agricultural extension system can enhance the agricultural productivity and production of smallholders through the development of innovative, systematic, and farmer-owned agricultural extensions. This study identified major constraints of adoption of agricultural extension package technologies such as adoption of inorganic and organic fertilizers, improved seeds, row planting, and crop protection chemicals at smallholder household level on sorghum crop production. The study used cross-sectional survey data collected from 201 sample respondent household farmers. To analyze data, descriptive statistics, ranking indexes, graphs, and tables were used. The study identified the major constraints of agricultural extension package technologies. High price, problem of on-time provision, shortage and uneven distribution of rainfall, and problem of accessibility were the major constraints that hinder the use of inorganic fertilizer. Using sources of organic fertilizer for other purposes, insufficient availability, undeveloped infrastructure, and facilities and requirement of more labor were the major constraints to the use of organic fertilizer.